Increased Hypocretin (Orexin) Plasma Level in Depression, Bipolar Disorder Patients - Li, Haimei; Lu, Jing; Li, Shangda; Huang, Bochao; Shi, Gongde; Mou, Tingting; Xu, Yi (Frontiers in Psychiatry, 2021)
As Hypocretin can markedly affect neurophysiological and behavioural processes in mood disorders. However, few studies have measured changes in hypocretin levels in patients with mood disorders. We estimated the hypocretin-1 plasma levels in mood disorder patients and controls (CON) using an enzyme-linked immunosorbent assay. Results: i) The hypocretin-1 plasma level was significantly higher in major depressive disorder (MDD) patients (59.04 (35.78-80.12) pg/ml, P<0.001) and bipolar disorder (BD) patients (65.50 (58.46-74.57) pg/ml, P<0.001) patients than in CON (49.25 (28.51-80.40) pg/ml). Moreover, the plasma hypocretin-1 levels in the BD group were significantly higher than those in the MDD group (P<0.001). ii). In the MDD group, patients with higher suicidal ideation had higher hypocretin-1 levels (62.09 (38.23-80.12) pg/ml) than those with lower suicidal ideation (59.63 (35.79-77.37) pg/ml), P=0.032). iii). Plasma hypocretin-1 levels were increased in both female and male mood disorder patients compared to CON (male: MDD 60.51 (35.79-80.12) pg/ml; BD 65.40 (58.76-74.14) pg/ml; CON 45.63 (28.51-62.05) pg/ml; all P<0.016; female: MDD 57.37 (34.59-80.40) pg/ml; BD 65.61 (58.46-74.57) pg/ml; CON 52.92 (38.23-78.89) pg/ml; all P<0.015). iv). In CON, we found a significant negative correlation between plasma hypocretin-1 levels and age (rho=-0.251, p=0.032), while this negative correlation was absent in the MDD and BD groups. Limitations may partly arise from the relatively small sample size and the medication history of patients participating in our research. We concluded that the clear changes found in plasma hypocretin-1 levels might be applied in the diagnosis of depression and the differential diagnosis of MDD and BD. The clear suicidal-ideation-related change found in hypocretin-1 levels in depression might be taken into account in the prevention of suicidal behaviour and further study of hypocretin-targeted therapies.